Joint Forest Management: Built on Rural India's Realities and Corresponding Scientific Conclusions - Time to Reconsider? - Rawat, Ashish; Chaudhary, B. L. (Indian Forester, 2000)
The rural poverty has increased by 10.16% 0991-1997) meaning the number of rural people currently living below the poverty line, are nearly 290 million. While embarking upon joint forest management experiments it is important to realize that the people living close to forests are still facing the fundamental problems like where they are going to get their next meal from. "Thin sampling" of JFM cases should be revisited in-depth to ascertain the processes, outcomes, and lessons for strengthening the cause of conservation. In fact it indicates the further research needs to strengthen the JFM institutions. The lack of capabilities deprives an individual! a group to take advantage of opportunities, and the same opportunities are likely to be squandered or misused by influential vested interests. Eorests&wildlife has evolved over centuries, and that is vanishing fast. To protect it, legal enforcement capabilities of the forest department are also strengthened to check the dominating vested interest while the greater understanding of the system, and its objectives, and the gradual and positive participation of every person at village level in JFM institutions is ensured. And, if JFM has to succeed further, there must be a well-conceived capacity building programme for all participants- people, NGOs, and foresters, supported by earnest scientific studies based on rural realities.